PENGARUH LOCUS OF CONTROL,GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI PADA KINERJA KARYAWAN BANK INDONESIA MALANG - Fatchurozi Fatchurozi; Hadi Sunaryo; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstrak This study aims to examine and analyze the influence of job locus of control, leadership style and organizasional comitment on employee performance of Indonesia Bank of Malang. The population and sample are all 32 employees. Data collection through questionnaire distribution. Data analysis in this research using SPSS version 16. Sampling technique using census method and data testing technique used in this research include validity test, reliability test, classical assumption test and multiple linear regression analysis, and hypothesis testing research.The results of the analysis show that the outline of locus of control affects the significance of employee performance on leadership styles that significantly influence employee performance as well as on organizational commitment has a significant effect. Together, it shows that locus of control, leadership style and organizational commitment significantly influence employee performance.